2008
DOI: 10.1159/000162664
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Media and Speech-in-Noise Recognition in School-Aged Children

Abstract: The present study examined the long-term consequences of otitis media (OM) on speech perception abilities in noise. 55 children with a prospective 3-monthly documented middle-ear status and hearing loss between birth and 24 months completed a ‘speech-in-noise’ (SPiN) test at the age of 7 years. Both hearing loss and the cumulation of uni- and bilateral OM incidents in early life were significantly correlated to the performance on the SPiN test at school age. Other background factors such as socio-economic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 48 publications
1
33
0
2
Order By: Relevance
“…Gravel and Wallace [1992] and Schilder et al [1994] have studied long-term effects of OM on language perception in background noise and found that performance in school-age children was correlated to early-life OM, years after middle ear problems had resolved. This has been found even in children born healthy without complications and normal cognitive and language development [Zumach et al, 2009]. Moreover, OM has been found to affect phonetic coding [Mody et al, 1999].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Gravel and Wallace [1992] and Schilder et al [1994] have studied long-term effects of OM on language perception in background noise and found that performance in school-age children was correlated to early-life OM, years after middle ear problems had resolved. This has been found even in children born healthy without complications and normal cognitive and language development [Zumach et al, 2009]. Moreover, OM has been found to affect phonetic coding [Mody et al, 1999].…”
Section: Introductionmentioning
confidence: 95%
“…While it is the actual hearing loss induced by OM rather than the number of OM episodes that is more sensitive to long-term consequences [Zumach et al, 2009; see also Schilder et al, 1994], hearing loss was not considered in the studies by Groenen et al [1996] and Clarkson et al [1989].…”
Section: Introductionmentioning
confidence: 99%
“…This argument was used to justify a study that also found no difference in the results of the binaural interaction test in children aged 6 years, who had the middle ear function monitored during the first years of life (7) . The third hypothesis is also related to the recurrence of episodes of OME, because a connection was established between the worst performance in the speech-in-noise test and the magnitude of fluctuating conductive hearing loss due to disease in the first years of life, and not the number of episodes of the disorder (14,15) . In this study, it was not possible to obtain back data on auditory acuity.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of recurrent OME (ROME) on hearing acuity in the short and long terms are well documented (6,7) . However, results on the auditory central nervous system (ANCS), despite the vast amount of information available, are controversial (2,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) . Studies focus on the premise of interdependence between episodes of OME and the change in tone thresholds, called fluctuating conductive hearing loss, because 80% children diagnosed with OME exhibit this kind of loss that acts as a sensory deprivation (8,15) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation